Developing a Comprehensive Digital Ecosystem Model to Enhance Competitive Advantage in Government-Fostered MSMEs - Murry Harmawan Saputra; Endah Pri Ariningsih (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
In response to the growing technological disruption, micro, small, and medium enterprises (MSMEs) require a comprehensive digital ecosystem as a crucial strategy to enhance their capabilities and competitiveness in a dynamic market. This study aims to develop and empirically validate a comprehensive digital ecosystem model grounded in the Resource-Based View (RBV) theory to enhance the competitive advantage of government-assisted MSMEs through optimizing the role of marketing performance. Based on the RBV theory, the research focuses on an in-depth analysis of four key elements of the MSME digital ecosystem: digital platform adoption capability, business incubator program effectiveness, MSME digital literacy, and collaboration capability. The research was conducted using a survey method on 238 MSME respondents from various sectors in Central Java, Indonesia. The research data were analyzed using Structural Equation Modeling (SEM-AMOS). The results prove that digital platform adoption, business incubator programs, digital literacy, and collaboration capabilities significantly affect MSMEs' marketing performance and competitive advantage. The implications of this research emphasize the importance of building a comprehensive MSME digital ecosystem by adopting technology, business incubator programs, digital literacy, and MSME collaboration capabilities to improve MSME competitiveness. This research contributes to the marketing management literature by expanding the application of the Resource-Based View theory in the context of MSMEs.